Effects of age and size on critical swimming speed of juvenile Chinese sturgeon Acipenser sinensis at seasonal temperatures. Issue 3 (4th February 2013) - He, X.; Lu, S.; Liao, M.; Zhu, X.; Zhang, M.; Li, S.; You, X.; Chen, J.
<x xml:space="preserve">Abstract</x> Changes in the critical swimming speed (Ucrit, cm s−1) with ontogeny of 2·5–12·5 month‐old juvenile anadromous Chinese sturgeon Acipenser sinesis were measured in a modified Blazka‐type swimming tunnel. The absolute Ucrit increased with length, mass and age; the relative U′crit (body lengths, s−1), however, decreased. Juvenile A. sinesis did not display a parr–smolt transformation at the length or age threshold to tolerate full‐strength seawater.